CIRI-CIRI KEPENGARANGAN DAN PENGGUNAAN LITERATUR DALAM MAJALAH INDONESIA BIDANG ILMU-ILMU SOSIAL - Sri Purnomowati (BACA: Jurnal Dokumentasi dan Informasi, 2004)
The pwpose of this study is to find out the authorshipand the use of literature characteristics in social sciences. Theresult for the study of Masyarakat Indonesia (JSSN 0125-9989)consists a number of 12 publications with 67 articles showingthat the authors were dominated by males. The most popularsubjects written are social groups by age and ethnic, and laboreconomics. The average number of authorship per article is1,09 and articles with multi authorship reaching 8,96% andauthor productivity being 9,23%. The average number of pagesper article is 19,60 pages and each article containing 24,91references. Books are the most used document for references,and median of all citation age is 11 years, while citation age inpolitics and economics are relatively current documents.Prisma is the most cited journal, while the most cited ofIndonesian authors is Koentjaraningrat.